Overcoming cultural taboo: A qualitative study of the untold lived experience of older adults' sexual life in Cebu, Philippines - Marjorie R. Sta. Teresa; Alain Kenneth S. Ragay; Alberich F. Machacon (Belitung Raya Foundation, 2024)
Background: The craving for sexuality and closeness continues into old age, although the means of expressing it may change. Beyond direct sexual encounters, older adults can express their sexuality through gentle affection, warm embraces, holding hands, and other intimate gestures. However, aging can also impact their sexual experiences. Objective: This study aimed to explore the lived experiences of sexuality among older adults living in the countryside of Cebu, Philippines, during their senior years. Methods: A qualitative descriptive phenomenological design was employed. Purposive sampling was used to select ten participants. Data were collected from September to December 2023, and Colaizzi's method of data analysis was applied to ensure thorough interpretation. Results: Three major themes emerged: 1) Being Centered: An actualized form of sexuality in later years; 2) Being Connected: A strong sense of intimacy in later years; and 3) Being Conveyed: Diversifying expressions of sexuality in later years. Conclusion: Despite advancing age, older adults can remain active in their intimate relationships and achieve a healthy marital life characterized by life satisfaction. They express their love for their partners by being centered, connected, and attuned to each other's needs and feelings. These findings highlight the importance for geriatric nurses to recognize and support the sexual health and intimacy needs of older adults, facilitating discussions and providing resources that promote overall well-being and quality of life.